2023
DOI: 10.1177/02692155231170451
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of health professionals on physical activity and sedentary behaviour in hospitalised adults: A systematic review and thematic synthesis

Abstract: Objective To explore health professionals’ perspectives on physical activity and sedentary behaviour of hospitalised adults to understand factors that contribute to these behaviours in this environment. Data sources Five databases (PubMed, MEDLINE, Embase, PsycINFO and CINAHL) were searched in March 2023. Review methods Thematic synthesis. Included studies explored perspectives of health professionals on the physical activity and/or sedentary behaviour of hospitalised adults using qualitative methods. Study el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 98 publications
0
2
0
Order By: Relevance
“…Studies of ICU clinicians, including nursing staff, suggest that health care providers believe that optimizing nighttime patient care workflow may be an opportunity for a sleep promotion intervention 30,31 . However, studies have also identified that a major barrier to decreasing inactivity and sedentary behavior in hospitalized patients is lack of adequate unit staffing to work closely with patients at high risk for cognitive decline and promote daytime activity 32 …”
Section: Discussionmentioning
confidence: 99%
“…Studies of ICU clinicians, including nursing staff, suggest that health care providers believe that optimizing nighttime patient care workflow may be an opportunity for a sleep promotion intervention 30,31 . However, studies have also identified that a major barrier to decreasing inactivity and sedentary behavior in hospitalized patients is lack of adequate unit staffing to work closely with patients at high risk for cognitive decline and promote daytime activity 32 …”
Section: Discussionmentioning
confidence: 99%
“…In addition to the risk of injury, another challenge for the nursing team engaging in patient mobilisation is the perception that mobilisation may not be an integral part of the nursing role (Alsop et al, 2023;Clarke, 2014;Intercollegiate Stroke Working Party, 2016;Kneafsey et al, 2013;Kneafsey & Haigh, 2009). A recent systematic review demonstrated that all health professionals, including nurses as the largest workforce, working on medical, surgical, geriatric and rehabilitation wards do not consider physical activity to be a priority (Alsop et al, 2023). A barrier to participation was that the promotion of physical activity across the 24-hour period was no one profession's defined responsibility.…”
Section: Introductionmentioning
confidence: 99%